Low absorption magnesium aluminate spinel windows for high energy laser applications. Issue 19 (14th October 2014) - Villalobos, Guillermo; Bayya, Shyam; Kim, Woohong; Baker, Colin; Sanghera, Jas; Hunt, Michael; Sadowski, Bryan; Miklos, Fritz; Aggarwal, Ishwar
Abstract